2020
DOI: 10.1016/j.clinph.2020.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Motor unit number index as an individual biomarker: Reference limits of intra-individual variability over time in healthy subjects

Abstract: Motor unit number index (MUNIX) variation depends on the experience of the operator. A 20% change in MUNIX sum score is significant. MUNIX could be used as a biomarker in the follow-up of neuromuscular disorders. a b s t r a c t Objective: Motor unit number index (MUNIX) is proposed to monitor neuromuscular disorders. Our objective is to determine the intra-individual variability over time of the MUNIX. Methods: In 11 different hospital centres, MUNIX was assessed twice, at least 3 months apart (range 90-360 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
(38 reference statements)
8
6
0
Order By: Relevance
“…In addition, the MUNIX correlated with muscle strength and disability score, confirming that weakness depends on the severity of denervation. Our results agreed with the results obtained for adults [55][56][57][58] and those obtained for pediatric patients with SMA reported recently. 59 The MUNIX technique had good intrarater variability among patients with Ped-SMA and was feasible for use with those patients compared with other electrophysiological techniques (CMAP amplitude and especially MUNE).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the MUNIX correlated with muscle strength and disability score, confirming that weakness depends on the severity of denervation. Our results agreed with the results obtained for adults [55][56][57][58] and those obtained for pediatric patients with SMA reported recently. 59 The MUNIX technique had good intrarater variability among patients with Ped-SMA and was feasible for use with those patients compared with other electrophysiological techniques (CMAP amplitude and especially MUNE).…”
Section: Discussionsupporting
confidence: 93%
“…Another very interesting aspect of this paper is the results in healthy children: they are similar to those in “younger” adults below 60 years of age 2,5,6 . Although the number of evaluated healthy children was very low, this might support the concepts that (a) lower motor neuron development is mature early in humans and (b) there is physiological loss of lower motor neurons after age > 60 years 2,6 …”
supporting
confidence: 63%
“…2,5,6 Although the number of evaluated healthy children was very low, this might support the concepts that (a) lower motor neuron development is mature early in humans and (b) there is physiological loss of lower motor neurons after age > 60 years. 2,6 Furthermore, Verma et al found the "reverse-split-hand" phenomenon in children with SMA, as shown previously in adult SMA patients. 7 This interesting finding shows us that diseases such as The existing therapeutic options for SMA are encouraging, however very costly, and an objective electrodiagnostic biomarker for disease progression in SMA might be an attractive additional outcome measure to track changes and drug effectiveness in children and adults with SMA.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Our work showed that MUNIX values correlated with muscle strength and CMAP amplitude. Since MUNIX scores closely depend on CMAP amplitude, which of the muscles is especially influenced by the placement of the electrodes, an experienced technician is essential ( 36 ). The sum of the results of deltoid, ADM, QF, and TA resulted in the MRC sum score and the MUNIX sum score.…”
Section: Discussionmentioning
confidence: 99%